Effect of Green Human Resource Practices on Organization Commitment - et al., Dr.Jyoshna.C (International Journal of Advanced Science and Technology, 2019)
There are many studies which showed that committed employees’ perform better. Every organization needs committed employees’ to attain objectives and with stand the competition. The study is related to Atlas Copco Ltd, Hyderabad. The sample unit is employees’ of Atlas Copco Ltd. The main purpose of the present study is to find the impact of green human resource practices on organization commitment levels of the employees’. The green Human Resource practices taken in the study are Leadership practice, Work culture, Recruitment and selection and Reward management. Regression is used for finding the association of green human resource practices and organization commitment. The findings of the study showed moderate positive impact of Green human resource practices on organization commitment. Leadership practice and work culture showed positive significant impact on organization commitment. Recruitment and selection, reward management was not having significant impact on the organization commitment levels of the employees.